Establishment of Hairy Root Transformation System for Evaluating Stress-Tolerant Gene in Jojoba - Bojing Li; Yan Wang; Wenguo Ma; Jie Bing; Yijun Zhou; Yuke Gen; Fei Gao (Agriculture)
Jojoba is an important tropical oil crop, and jojoba oil is widely used in the aerospace lubricant and cosmetic industries. Jojoba exhibits high tolerance to droughts and high temperatures. However, there is currently a lack of rapid and effective methods for identifying stress-tolerant genes in jojoba. Here, an efficient hairy root genetic transformation system of jojoba (Simmondisa chinensis) mediated by Agrobacterium rhizogenes was established and used for the functional evaluation of ScGolS1, a putative stress-tolerant gene. First, using the leaves of jojoba as explants, transgenic jojoba hairy roots carrying the RUBY gene were obtained under sterile conditions using the “soaking co-cultivation method”. Second, we optimized the four conditions affecting hairy root genetic transformations, namely, the strains of A. rhizogenes, co-cultivation under light or dark conditions, the infection time, and the OD600 value of the bacterial suspension. The following best transformation conditions were determined, A. rhizogenes K599, light during co-cultivation, an infection time of 10 min, and bacterial suspension OD600 = 0.6, under which the transformation rate could reach 27%. Third, based on the “soaking co-cultivation method”, a new method called the “wrapping co-cultivation method” was developed, which does not require tissue cultures and can induce transgenic hairy roots of jojoba in two months. Using the “wrapping co-cultivation method”, we successfully obtained transgenic hairy roots overexpressing the ScGolS1 gene, which exhibited higher tolerance to low-temperature stress. A hairy root-based genetic transformation system of jojoba will promote the functional genomics and molecular breeding of jojoba.